Organoleptic Test of Boba Flour Substitution of Pumpkin Seeds High in Fiber and Protein - Maurizka Sabrina Septia; Septa Katmawanti; Supriyadi Supriyadi (Journal of Healthcare and Biomedical Science, 2022)
In 2013, the obesity rate in Indonesia for people over the age of 18 was 14.8 percent; by 2018, the obesity rate had risen to 21.8%. The significant number of fat people in Indonesia is caused by high sugar consumption and low fiber consumption regularly. 100 grams of pumpkin seeds contain 6 grams of fiber, 30.23 grams of protein, 7.2 mg/100 zinc, polyunsaturated fatty acids, and phytosterols. The purpose of this study is to identify the panelists' level of preference for four formulations of pumpkin seed flour boba using assessment factors such as taste, color, texture, and aroma. The procedural model was used in this research and development. This development study utilizes an opinion-based process, which is then modified based on research needs. Organoleptic testing on boba products without added milk drinks on untrained panelists revealed a significant difference in color and texture parameters. There was no significant difference in panelist acceptability of aroma and taste characteristics. The findings of the untrained panelist's appraisal of boba added to a milk companion drink were then presented, revealing significant changes in the color and texture parameters. Furthermore, there were no statistically significant changes in the aroma and taste indices.